Partisipasi Politik Masyarakat pada Pemilihan Umum Legislatif 2014 di Daerah Pemilihan Banggai III - Halim, Rahmawati (Jurnal Review Politik, 2016)
This study aims to determine the extent to which the social participation of the community in legislative elections and to find out several factors that affect the high number of people who are not involved in the legislative elections in the electoral district Banggai III in April 9, 2014. Research locations are in six districts; Bualemo, Pagimana, Lobu, Bunta, Nuhon, and Simpang Raya, with a research population of 101.296 people, and the total sample of the study was 236 people. The results show that inadequate matters can be seen in 61% legislative election voting, 36% political discussion activity, 47% campaigning, 30% other group activities, and 37% individual communications. The results also show that positive and significant effects on society are social and economic status, geographical situation, parent affiliation, organization, political awareness, and encouragement to the government.